Detection of genomic loci associated with days to heading in tropical japonica rice through QTL-seq - Khairul Yusuf Nasution; Dani Satyawan; Muhamad Yunus; Azri Kusuma Dewi; Puput Melati; Marina Yuniawati Maryono; Ita Dwimahyani; Wening Enggarini; Sobrizal (Czech Journal of Genetics and Plant Breeding)
This study investigated the genetic basis of days to heading (DTH) in tropical japonica rice using F2 populations derived from late-maturing Rojolele and early-maturing Rojolele Srinuk varieties. Phenotypic analysis of DTH showed continuous distribution and positive skewness. Whole genome sequencing (WGS) derived single nucleotide polymorphism (SNP) from early and late-heading bulks were used to identify three candidate regions with strong association to DTH: qDTH3.1 and qDTH3.2 on chromosome 3, and qDTH7.1 on chromosome 7, with the latter linked to the Oryza sativa Pseudo-Response Regulator 37 (OsPRR37) gene. InDel markers validated qDTH7.1's significant linkage to DTH, particularly marker ID14, which is effective for marker-assisted selection of early DTH in Rojolele background.